Does Local Government’s Spending Effective in Improving Human Development Index? Study in Underdeveloped Region - Siswantoro Siswantoro (Salus Cultura: Jurnal Pembangunan Manusia dan Kebudayaan, 2023)
The purpose of this study was to examine each local government expenditure in the health, education, and economic functions against three indicators forming the Human Development Index (HDI) as a measure to assess community welfare, namely health, education, and economic indicators in 122 underdeveloped regions in Indonesia from 2015-2018 period. The HDI health indicator is measured using Life Expectancy (UHH), the education indicator is represented by School Year Expectation (HLS), and the economic indicator is represented by Population Expenditure per Capita (PPK). In addition, other variables that can affect HDI are included, namely poverty and population growth. The research method used multiple linear regression analysis with the selected model, namely the fixed effect model (FEM). This study used 488-panel data consisting of a combination of 122 cross-sectional data originating from 122 underdeveloped regencies/cities in Indonesia and time series data for 4 years from 2015-2018. The results showed that only local government expenditures in economic function had a positive and significant effect on the HDI economic indicators, namely PPK. If government spending on economic functions increases by 1%, it can increase the expenditure per capita of residents in underdeveloped areas in 2015-2018 by 0.03102%. Meanwhile, local government spending in the health function does not have a significant effect on UHH, and local government spending in the education function does not have a significant effect on HLS. Another result shows that the poverty variable has a negative and significant effect on all HDI indicators in underdeveloped areas.